2019
DOI: 10.1590/1678-5150-pvb-6273
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection by Anaplasma marginale in buffaloes and cattle: clinical, hematological, molecular and pathological aspects

Abstract: The study aimed to evaluate and compare the clinical, laboratory and pathological aspects of buffalo and bovine experimentally infected with AmRio 2 strain of Anaplasma marginale. Four Murrah buffaloes and four crossbred cattle were used in the experiment, which two animals of each species were splenectomized. Strain AmRio 2 of A. marginale was inoculated in all experimental animals. Clinical exams, Packed Cell Volume (PCV), blood counts, blood smears, rickettsemia, necropsy and histopathology were performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
4
2
0
Order By: Relevance
“…Although clinical signs have been reported in some experimental studies (Sharma ,1987;Reddy et al, 1988) and natural infections (Srivastava and Ahluwalia, 1974;Vatsya et al, 2013) in buffaloes, however, in other investigations that have been done in this area, similar results to the present study have been reported in which A. marginale only caused subclinical infection with low parasitemia in river buffaloes (Singh and Gill, 1977;Guatam et al, 1970;Obregón et al, 2018). In addition, in an experimental study, buffalo infestation with A. marginale was associated with no clinical and blood abnormalities and also lower frequency of infection in blood PCR tests compared to cattle (Lima et al, 2019). Hence the researchers suggested that buffaloes may be an alternative to raising cattle in areas with high frequency of clinical anaplasmosis (Lima et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although clinical signs have been reported in some experimental studies (Sharma ,1987;Reddy et al, 1988) and natural infections (Srivastava and Ahluwalia, 1974;Vatsya et al, 2013) in buffaloes, however, in other investigations that have been done in this area, similar results to the present study have been reported in which A. marginale only caused subclinical infection with low parasitemia in river buffaloes (Singh and Gill, 1977;Guatam et al, 1970;Obregón et al, 2018). In addition, in an experimental study, buffalo infestation with A. marginale was associated with no clinical and blood abnormalities and also lower frequency of infection in blood PCR tests compared to cattle (Lima et al, 2019). Hence the researchers suggested that buffaloes may be an alternative to raising cattle in areas with high frequency of clinical anaplasmosis (Lima et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, in an experimental study, buffalo infestation with A. marginale was associated with no clinical and blood abnormalities and also lower frequency of infection in blood PCR tests compared to cattle (Lima et al, 2019). Hence the researchers suggested that buffaloes may be an alternative to raising cattle in areas with high frequency of clinical anaplasmosis (Lima et al, 2019). Other studies similarly reported lower values of natural infection in buffaloes (Silva et al 2014a(Silva et al , 2014b in comparison to the detected in cattle (Bacanelli et al 2014).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Congestion and haemorrhages were also observed. In overall, the histopathological changes observed in the present study are in agreement with previous reports (Jaswal et al, 2015;Abba et al, 2016;Lima et al, 2019). It is well known that anoxia causes degenerative changes and necrosis in parenchymatous organs.…”
Section: Histopathological Observationssupporting
confidence: 93%
“…The post mortem examination also revealed presence of severely congested lungs (Fig 2D ), hepatomegaly with blunt edges and necrosis (Fig 2E), splenomegaly with discoloration (Fig 2F ) and distended gall bladder with dark colored bile (Fig 2G). Pulmonary congestion, distension of gallbladder, enlargement of liver and spleen has been documented in both natural and experimental bovine anaplasmosis (Jaswal et al, 2015;Abba et al, 2016;Lima et al, 2019). Splenomegaly with congestion and discoloration reported in the present study may be due to erythrophagocytosis that results in excessive destruction of defective erythrocytes by macrophages within the spleen (Devos et al, 2006).…”
Section: Gross Lesionssupporting
confidence: 55%